Safe discharge: an irrational, unhelpful and unachievable concept - Goodacre, S (BMJ Group, 2006)
Emergency doctors often decide whether to advise hospital admission or discharge by assessing whether a decision to discharge home is considered safe. This implies that hospital admission may be recommended on the basis of exceeding an arbitrarily defined risk of adverse outcome, rather than weighing the potential benefits, risks and costs of hospital admission. This approach is likely to lead to irrational decision making, unnecessary hospitalisation and unrealistic expectations regarding risk. Instead of using the concept of a safe discharge, we should take a more rational approach to decision making, weighing the benefits, risks and costs of hospitalisation against a default option of discharge home. Hospital admission should be recommended only if the expected benefits outweigh the risks and can be accrued at an acceptable cost. Guidelines should be developed using this approach and used to promote and support rational decision making.